2004
DOI: 10.1038/sj.ejcn.1601845
|View full text |Cite
|
Sign up to set email alerts
|

Association of subclinical vitamin D deficiency with severe acute lower respiratory infection in Indian children under 5 y

Abstract: Objectives: To determine whether subclinical vitamin D deficiency in Indian children under 5 y of age is a risk factor for severe acute lower respiratory infection (ALRI). Design: A hospital-based case-control study. Setting: Sanjeevani Paediatrics Hospital, a private hospital in Indapur, India. Participants: A total of 150 children including 80 cases and 70 controls, aged 2-60 months, were enrolled. Case definition of severe ALRI as given by the World Health Organization was used for cases. Controls were heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
307
3
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(341 citation statements)
references
References 20 publications
18
307
3
13
Order By: Relevance
“…In Finland soldiers with low vitamin D status (,40 nmol/l) at entry into military service have a higher risk for subsequent respiratory infections (31) . Similar results are reported also in Turkey (32) and India (33) , where levels below 50 nmol/l significantly increased the risk of respiratory infections in children and neonates. A recent American study reports 55 % higher odds of developing respiratory infections if 25(OH)D concentration is below 25 nmol/l compared with above 75 nmol/l (34) .…”
Section: Discussionsupporting
confidence: 88%
“…In Finland soldiers with low vitamin D status (,40 nmol/l) at entry into military service have a higher risk for subsequent respiratory infections (31) . Similar results are reported also in Turkey (32) and India (33) , where levels below 50 nmol/l significantly increased the risk of respiratory infections in children and neonates. A recent American study reports 55 % higher odds of developing respiratory infections if 25(OH)D concentration is below 25 nmol/l compared with above 75 nmol/l (34) .…”
Section: Discussionsupporting
confidence: 88%
“…The ocular signs of VAD include night blindness, conjunctival xerosis, Bitot spots, corneal ulceration, keratomalacia and total blindness. Several studies have revealed that there is a positive association between VAD and increased respiratory infections (2,3) , diarrhoea, measles and childhood mortality (4)(5)(6)(7)(8)(9) . VAD compromises the immune system in 40 % of children in the developing world and contributes to one million deaths of young children each year (10,11) .…”
mentioning
confidence: 99%
“…In recent years there have been several reports on the associations between subclinical vitamin D deficiency and risk for respiratory infections and development of more severe disease (2)(3)(4). Different immunomodulatory effects may explain these associations (5).…”
mentioning
confidence: 99%